Implementasi Akuntansi Sumber Daya Manusia Pada PT. Perkebunan Nusantara III (Persero) Medan - Rizky Ananda Dafitra Siregar; Nurlaila Nurlaila (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Human resource accounting is considered strategic because employees are not only considered as operational costs, but also as assets that make a real contribution to the company's success. This means that human resource management does not only revolve around recording employee-related expenses, but also involves measuring the added value provided by the workforce towards achieving company goals. This research uses a descriptive qualitative research method, in the research "Implementation of Human Resources Accounting at PT. Perkebunan Nusantara III (Persero) Medan," this research will focus more on an in-depth understanding of various aspects of the implementation of human resources (HR) accounting in the company. . It can be concluded that this company has succeeded in managing human resources (HR) through the human resource accounting function with a structured approach. Involving employee performance measurement, value identification, and contribution costs, the company shows a commitment to measurable HR management. The strategy aims to create an environment where employees feel valued and can make significant contributions.